Analisis Likuiditas, Profitabilitas, dan Ukuran Perusahaan terhadap Perubahan Laba pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di BEI - Eko Prasetyo; Petty Arisanti (P3M Politeknik Negeri Banjarmasin, 2021)
This study was conducted to determine how the effect of liquidity as measured by the Quick Ratio, profitability as measured by Net Profit Margin, and Firm Size on Profit Changes. The type of data used is secondary data obtained from the publication of performance summaries listed on the Indonesian Stock Exchange (IDX). The population in this study are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2018-2020, totaling 37 companies. The sampling technique used is purposive sampling which is then obtained as many as 25 samples of companies. The data analysis technique in this study is multiple linear regression analysis with a 5% confidence level. The results showed that the variables of profitability and firm size had a significant effect on changes in earnings, while the liquidity variables had no significant effect on changes in profits. Based on the results of the F test, it is known that all independent variables simultaneously have a significant effect on changes in earnings.